Climate and air quality co-benefits of improving taxi system in Ha Long city, Quang Ninh - Dung, Nghiem Trung; Anh, Ho Tuan (Vietnam Journal of Science and Technology, 2014)
Co-benefits of improving taxi system in Ha Long city, Quang Ninh province were studied. Three areas and nine routes in the urban area of Ha Long were selected for conducting this study. Information on the technical specifications of the taxi system was collected by 130 questionnaires. Taxi volume on nine selected routes was determined by vehicle counting. Real-time information on the driving behavior of taxis was obtained by GPS. Collected data were processed to generate input files to run IVE model associated with the base state and 4 selected air pollution control scenarios. Emission factors of air pollutants of the taxi system in Ha Long for these cases were determined. Climate and air quality co-benefits were assessed. Keywords: Co-benefit, Ha Long, IVE model, taxi, air quality, climate, emission factor.